A Mass Ratio of Hierarchical H-ZSM5 And Fatty Acid Methyl Ester of Cerbera Manghas Oil and The Effect on The Hydrocarbon Liquid Product Composition - Sutrisno Sutrisno; Rahmi Rahmi; Lenny Marlinda; Muhammad Al Muttaqii; Cyndy Dwi Afrila; Yanuar Fasmawi; Yuli Evrianti (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2022)
Fossil fuels are classified as non-renewable resources. On the other hand, using fossil fuels has further aggravated the impact of the environmental crisis. The development of alternative fuels that are renewable and renewable is urgently needed in line with the increasing need for fuel. One alternative energy source that can be used in the development of biofuels is Cerbera manghas oil. The catalytic cracking process with 178 g of Cerbera manghas oil can be carried out using hierarchical H-ZSM-5 as a catalyst with a mass of 0.1, 0.2, 0.3, 0.4, and 0.5g at a temperature of 250℃. Gas Chromatography Analysis–Mass Spectrometry (GC-MS) was performed on Cerbera manghas oil and biofuel products. Several hydrocarbons, C7-C12 and C16-C17, with the largest content, were identified as diesel (29.14%) and gasoline (14.08%) using a catalyst mass of 0.5g. So that the use of hierarchical H-ZSM-5 catalyst in the catalytic cracking of Cerbera manghas oil can produce hydrocarbon range gasoline.